PENGARUH EXECUTIVE COMPENSATION, MANAGERIAL OWNERSHIP DAN PROFITABILITY TERHADAP EARNINGS QUALITY - Frisca Angela; Nurainun Bangun (Jurnal Paradigma Akuntansi, 2023)
This research aims to see the effect of executive compensation, managerial ownership, and profitability on earnings quality. The profit contained in the financial statements of a company aims to be a benchmark as a performance appraisal by the company as a basis for decision making by the company, so that many companies commit fraud against financial statements. Earnings quality is the answer to determine the accuracy of earnings in the financial statements made by the company. This study uses a population of manufacturing companies listed on the Indonesia Stock Exchange which provides complete data on the variables studied during the 2018-2020 period, and 141 observations were selected from 2018 to 2020. In this study it was found that executive compensation and managerial ownership proved to have no effect on earnings quality. Meanwhile, this study shows that profitability is proven to have an effect on earnings quality.